The Quality of Working Life, Organizational Commitment and Learning Agility Affecting the Organizational Performance of State University in Phitsanulok Province - Siwnguan, Juraput; Chamlongrath, Wichitra; Ngamsuthi, Jirapa (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2024)
This research investigated the quality of working life, organizational commitment, and learning agility that affected the organizational performance of the state universities in Phitsanulok Province. The objective of this study was to examine the influence of the quality of working life, organizational commitment, and learning agility on the organizational performance of the state universities in Phitsanulok Province. The 376 participants were universities’ academic personnel and academic support staff. Descriptive statistics and multiple regression analysis were employed for data analysis. The results revealed that the quality of working life, organizational commitment, and learning agility influenced the organizational performance of the state universities in Phitsanulok Province at a statistical significant level of 0.05.Additionally, it was found that organizational commitment influenced the organizational performance at a highest level, followed by quality of working life, and learning agility. Also, the forecasting equation was able to predict the organization's performance with an accuracy of 76.70 percent.